A-charting students' academic performance - Mohd. Noor, Fatimah; Abdul Mukti, Mohamad Afifi (2005)
Universiti Teknologi Malaysia started offering academic programmes at Bachelor level in 1969. It was then implemented according to the term system. In 1980's the term system was replaced by the semester system, which was quite similar to that implemented in the United States. The UTM semester system requires a set menu of subjects offered in every semester. A student has a minimum- maximum duration of stay and minimum- maximum number of credits to be taken in each semester. The whole idea is to limit the work pressure on a student, and to ensure that he/she has sufficient hours of self-study in order to secure all the credits taken. However, there had been incidents whereby average students with ‘strong desires’ tried to swallow more than what they could chew. Of course, the end result was very unfavourable. They failed to graduate. This paper highlights the use of the A-Chart in monitoring students’ performance. It has been widely used as a guide by the Faculty of Mechanical Engineering, UTM since 1980’s. It assists the academic advisors and management to monitor each individual student’s performance at a glance, and to be able to make a forecast as to the possibility of the student graduating. The A-Chart is divided into two significant zones, i.e. safe and unsafe, whether the student will ultimately graduate during the prescribed semester or has to go for the optional extension of time, or will not graduate at all, respectively, unless some other assistance are given. An example is illustrated.